2021
DOI: 10.1098/rspb.2021.0500
|View full text |Cite
|
Sign up to set email alerts
|

More than words: word predictability, prosody, gesture and mouth movements in natural language comprehension

Abstract: The ecology of human language is face-to-face interaction, comprising cues such as prosody, co-speech gestures and mouth movements. Yet, the multimodal context is usually stripped away in experiments as dominant paradigms focus on linguistic processing only. In two studies we presented video-clips of an actress producing naturalistic passages to participants while recording their electroencephalogram. We quantified multimodal cues (prosody, gestures, mouth movements) and measured their effect on a well-establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 72 publications
6
50
1
Order By: Relevance
“…We identified interactions between gesture, mouth informativeness, and clarity, supporting proposals in which auditory and visual cues are dynamically and flexibly weighted during communication (Skipper et al, 2009;Zhang, Frassinelli, et al, 2021b). In one of the first experimental studies looking at audiovisual (including gestures) speech, Drijvers and Özyürek (2017) demonstrated that moderately noisevocoded speech comprehension was enhanced when the two cues were present, with iconic gestures having a larger effect than mouth movements.…”
Section: Dynamic Interplay Between Speech Gesture and Mouth Movementssupporting
confidence: 73%
See 3 more Smart Citations
“…We identified interactions between gesture, mouth informativeness, and clarity, supporting proposals in which auditory and visual cues are dynamically and flexibly weighted during communication (Skipper et al, 2009;Zhang, Frassinelli, et al, 2021b). In one of the first experimental studies looking at audiovisual (including gestures) speech, Drijvers and Özyürek (2017) demonstrated that moderately noisevocoded speech comprehension was enhanced when the two cues were present, with iconic gestures having a larger effect than mouth movements.…”
Section: Dynamic Interplay Between Speech Gesture and Mouth Movementssupporting
confidence: 73%
“…Thus, the face is cropped or covered in studies of gestures (e.g., Drijvers & Özyürek, 2017;Habets et al, 2010;Hirata & Kelly, 2010;Holle & Gunter, 2007;Holle et al, 2010), and the hands are not visible in studies of audiovisual speech (e.g., Ross et al, 2007;Solberg Økland et al, 2019;Tye-Murray et al, 2007). Only a handful of studies have investigated both gestures and mouth movements (Drijvers & Özyürek, 2017(Drijvers & Özyürek, , 2020Drijvers et al, 2019;Hirata & Kelly, 2010;Skipper et al, 2009;Zhang, Ding, et al, 2021a;Zhang, Frassinelli, et al, 2021b).…”
Section: Weighting the Multimodal Cuesmentioning
confidence: 99%
See 2 more Smart Citations
“…ECAs are virtual entities that can convey messages and engage in conversation in a human-like manner by using speech, language, gestures, and facial expressions [ 16 ]. While verbal channels carry symbolic/semantic interpretation of the message, the non-verbal channels (i.e., gestures, facial expressions, and prosody) serve as an orchestrator of communication and are integral to comprehension [ 17 , 18 ]. By incorporating features such as facial expressions and gestures, social links between humans and their virtual counterparts may be established.…”
Section: Introductionmentioning
confidence: 99%